Constant Beauty Within and PCOS as Cacti - Stokes, Grace (BioéthiqueOnline, 2016)
PCOS as CactiCactuses, flowers, spray paint, glittersvarious sizesandConstant Beauty WithinScreen printing (1)59 x 84 cmDigital prints (3)42 x 29,50 cm